Burden, profile and care: caregivers of socially vulnerable elderly persons - Isabela Thaís Machado de Jesus; Ariene Angelini dos Santos Orlandi; Marisa Silvana Zazzetta (Revista Brasileira de Geriatria e Gerontologia, 2018)
Abstract Objectives: To compare burden and sociodemographic profile and to analyze the care needs of caregivers of elderly persons enrolled in Social Care Referral Centers in a municipal region in the interior of the state of São Paulo, Brazil. Method: A cross-sectional, quantitative-qualitative study was carried out. A sociodemographic questionnaire, the Zarit Burden Scale and three open questions regarding care needs were applied. The quantitative data were analyzed by descriptive statistics and the correlation test. The hermeneutic-dialectic referential was applied and the qualitative data were analyzed by the content analysis technique. Results: A total of 86 caregivers participated in the study. The majority were female (71.7%), had a mean age of 56.5 (sd=14.9) years, suffered burden and lived in vulnerable neighborhoods. With regard to care, the provision of support for activities of daily living, difficulties in caring and the help of other relatives were identified. Burden negatively correlated with age range and schooling (r=-0.11; r=-0.87). Conclusion: Guidance and the acquisition of caring skills remain unprovided by the resources and services that exist in vulnerable contexts, and resolutive support strategies are lacking in public facilities.